USE OF NEW GROUPS OF CORTICOSTEROID OINTMENTS IN THE TREATMENT OF PATIENTS WITH NEURODERMITIS (ATOPIC DERMATITIS) - ISLAMOV NURALI HIKMATOVICH; ERMANOV RUSTAM TEMIROVICH (PEDAGOGS, 2024)
Abstract: Data on the mechanisms of formation and methods of effective treatment of atopic dermatitis (AD) are presented. The main directions of pathogenetically based treatment of blood pressure, differentiated correction of concomitant pathology are described in detail. The external therapy of atopic skin lesions in children with the use of modern dermatological cosmetics is presented in particular detail.